2017
DOI: 10.1093/nar/gkx1154
|View full text |Cite
|
Sign up to set email alerts
|

The European Bioinformatics Institute in 2017: data coordination and integration

Abstract: The European Bioinformatics Institute (EMBL-EBI) supports life-science research throughout the world by providing open data, open-source software and analytical tools, and technical infrastructure (https://www.ebi.ac.uk). We accommodate an increasingly diverse range of data types and integrate them, so that biologists in all disciplines can explore life in ever-increasing detail. We maintain over 40 data resources, many of which are run collaboratively with partners in 16 countries (https://www.ebi.ac.uk/servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…Empirical data suggests that nucleotide and proteomics data generation is growing at an exponential rate. Researchers at the European Bioinformatics Institute (EMBL‐EBI) have monitored the growth of the different types of data stored in their servers and concluded that it is doubling roughly every year (see Figure ). This exponential growth raises significant challenges to the organizations that have the mission of storing and organizing such data but provides a bounty for biotechnology researchers who have the ability to explore and exploit the ever‐increasing information stored in servers, worldwide.…”
Section: The Rapid Growth Of Biological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical data suggests that nucleotide and proteomics data generation is growing at an exponential rate. Researchers at the European Bioinformatics Institute (EMBL‐EBI) have monitored the growth of the different types of data stored in their servers and concluded that it is doubling roughly every year (see Figure ). This exponential growth raises significant challenges to the organizations that have the mission of storing and organizing such data but provides a bounty for biotechnology researchers who have the ability to explore and exploit the ever‐increasing information stored in servers, worldwide.…”
Section: The Rapid Growth Of Biological Datamentioning
confidence: 99%
“…Growth of data stored by EMBL‐EBI, for different types of data. Reprinted from Cook et al, with permission.…”
Section: The Rapid Growth Of Biological Datamentioning
confidence: 99%
“…The main archives for cellular structural biology are EMDB (tomograms) and Electron Microscopy Public Image Archive (EMPIAR) [9] (raw data related to EMDB entries, as well as 3D reconstructions from other bioimaging techniques that are not supported by EMDB, such as 3D-SEM and SXT). EMBL-EBI [10] is directly involved in the running and operation of all these archives, with the exception of BMRB and SASBDB (with whom we collaborate). URLs for the websites of the archives mentioned here and in the following section can be found in Table 1.…”
Section: Structural Biology Is Well Served By Free and Open Archival mentioning
confidence: 99%
“…Archiving and indexing large datasets is a nontrivial, but a possible task, as demonstrated by the plethora of database repositories currently in use for biology research, electron microscopy, microarray analysis, radiology, or multidiscipline research …”
Section: Introductionmentioning
confidence: 99%